1996
DOI: 10.1021/jm960162z
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Characterization of Pyrrolo[2,1-d][1,5]benzothiazepine Derivatives Binding Selectively to the Peripheral-Type Benzodiazepine Receptor (PBR):  From Dual PBR Affinity and Calcium Antagonist Activity to Novel and Selective Calcium Entry Blockers

Abstract: The synthesis and cardiovascular characterization of a series of novel pyrrolo[2,1-d][1,5]-benzothiazepine derivatives (54-68) are described. Selective peripheral-type benzodiazepine receptor (PBR) ligands, such as PK 11195 and Ro 5-4864, have recently been found to possess low but significant inhibitory activity of L-type calcium channels, and this property is implicated in the cardiovascular effects observed with these compounds. In functional studies both PK 11195 (1-(2-chlorophenyl)-N-methyl-N-(1-methylpro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 54 publications
1
28
0
Order By: Relevance
“…PBOX-6 (7-[(dimethylcarbamoyl) oxy]-6-(2-naphthyl)pyrrolo-[2,1-d][1,5]benzoxazepine) and PBOX-15 (4-acetoxy-5-(-1-(naphthyl)naphtho [2,3-b]pyrrolo [2,1-d] [1,4]oxazepine) were synthesized as described previously (Campiani et al, 1996) and dissolved in ethanol. Structures of the PBOX compounds were described by Mulligan et al (2006).…”
Section: Methodsmentioning
confidence: 99%
“…PBOX-6 (7-[(dimethylcarbamoyl) oxy]-6-(2-naphthyl)pyrrolo-[2,1-d][1,5]benzoxazepine) and PBOX-15 (4-acetoxy-5-(-1-(naphthyl)naphtho [2,3-b]pyrrolo [2,1-d] [1,4]oxazepine) were synthesized as described previously (Campiani et al, 1996) and dissolved in ethanol. Structures of the PBOX compounds were described by Mulligan et al (2006).…”
Section: Methodsmentioning
confidence: 99%
“…In a separate study, the authors described the synthesis and cardiovascular characterization of a number of previously developed [70,71] or newly synthesized pyrrolo[2,1-d] [1,5]-benzothiazepine derivatives [97]. Indeed, selective TSPO ligands, such as Ro 5-4864 (2) and PK 11195 (3), have been found to possess low but significant inhibitory activity of L-type calcium channels, producing beneficial cardiovascular effects.…”
Section: Benzodiazepine Benzothiazepine and Benzoxazepine Derivativesmentioning
confidence: 99%
“…Subsequently, to evaluate the consistency of the SAR trends, the basic structure of compounds (95)(96)(97) was subjected to structural modifications in three of the four postulated pharmacophoric groups ( 1, LA, FRA), to give compounds 98-102, Table 9 [111]. Although a general decrease in TSPO affinity was observed with respect to the parent compounds, almost all the new derivatives showed TSPO affinities in the nanomolar range, with a modulation suitable for a SAR analysis, that find correlations with previous reports, Table 9.…”
Section: Three Lead Compounds Selected From This Series Nn-din-propmentioning
confidence: 99%
“…To explain these results, it has been suggested that Ro5-4864 also possesses a low affinity for the voltage-operated calcium channels and that at micromolar concentrations, it can probably compete for the same BDZ-binding site on voltage-operated calcium channels. 32,33 These observations suggest that at high concentrations, midazolam possesses the calcium-channel antagonist property of acting directly on voltage-operated calcium channels. 12,17,[34][35][36][37] The calcium-antagonist property of midazolam supports the endothelium-independent mechanism of midazolam-induced vasodilation that we observed in this study.…”
Section: Discussionmentioning
confidence: 97%